The Impact of Leadership in Gender Diversity of Annual Meeting Speakers in the American Society for Surgery of the Hand - Minji Kim, BS; Ines C. Lin, MD, MSEd, FACS; Helen G. Hui-Chou, MD, FACS (Journal of Hand Surgery Global Online)
Purpose: The American Society for Surgery of the Hand (ASSH) is the largest membership organization for hand surgeons. In 2022, the ASSH annual meeting had a man president and men program chairs. In 2023, the ASSH annual meeting was led by a woman president and women co-chairs. In this study, we aimed to compare the gender and racial diversity of speakers and moderators between these 2 years. Methods: The programs for ASSH for 2022 and 2023 were collected from web searches and ASSH Annual meeting programs. Gender and race for each speaker were discerned based on perceived visual perceptions from photographs. Chi-square tests were performed to compare the gender and racial diversity between 2022 and 2023. Results: There were 620 and 587 speaking opportunities in years 2022 and 2023, respectively. Proportion of women speakers significantly increased from 23.1% to 33.2%, as did the proportion of women moderators (18.6% vs 38.0%). Racial distribution did not significantly change between 2022 and 2023. Percentages of panels with at least one woman speaker significantly improved between the two time points, from 66.7% to 87.1%. Conclusions: We found significant increases in the proportion of women speakers and panels with at least one woman speaker between the 2022 and 2023 annual meetings (P < .001). We propose that leadership diversity in annual meeting planning may account for these changes. Therefore, we encourage ongoing efforts to diversity through annual meeting planning and leadership committees as one strategy to achieve diversity, equity, and inclusion in our field. Type of study/level of evidence: Observational III.